Potencial de utilização de biochars de resíduos da agroindústria para recuperação de voçorocas - Veiga, Taís Regina Lima Abreu (2021)
The objective of this work was to evaluate the potential use of biochars produced with agro-industrial residues in the gully’s recovery process. Specifically: (i) chemically and physically characterize biochars produced from agro-industrial residues at different temperatures, (ii) evaluate the modifications that occurred in the soil-sediment after its application and (iii) evaluate the effect of biochar on plant development indicator grass Vetiveria zizanioides L. For better conduction and execution, the thesis was developed in two stages. In the first stage, coffee husk biochars (CC), chicken litter (CF), sugarcane bagasse (BC) and corn straw (PM) were produced at temperatures of 350 and 450ºC. The materials were evaluated for their chemical and physical characteristics. The results obtained indicate that there was influence of temperature on the chemical and physical properties of biochars. The CC and CF biochars showed higher nutrient content, cation exchange capacity (CTC), electrical conductivity and ash, which demonstrates greater potential to correct soil nutritional deficiencies. BC and PM biochars had higher carbon content and aromatic groups, indicating that they are more suitable for soil nutrient immobilization and CTC increase. In the second stage, soil-sediment from an active gully was collected, at horizon C, which was also characterized in terms of its physical and chemical attributes. The soil-sediment was incubated for 30 days with different doses of biochars, in order to evaluate the effect of the treatments on its fertility. The experimental design was completely randomized, consisting of 5 biochars, 2 pure (CC and CF) + 3 mixtures (CC+CF, CC+BC, CF+BC) x 6 concentrations (5 different concentrations v/v (0, 5.1;2;5;10%) + control) x 4 repetitions, totaling 104 samples. The indicator plant used was the grass Vetiveria zizanioides L, which was evaluated for its development in aerial part and root. There was a significant increase in soil-sediment fertility as the concentration of biochars increased. The best results of the incubation test were for the treatments CF, CC+CF, CC, mainly due to the large amount of ash and nutrients present in this type of biochar, which promoted considerable increases in pH, in the amount of phosphorus and potassium available. Regarding the effect of treatments on indicator plant development, CC+BC and CF+BC, mainly at 5%, were the ones that showed the best results, providing an increase of up to four times in the amount of total plant dry mass.